Der Atlas der ungarischen Dialekte in Rumänien steht vor der Vollendung - Juhász, Dezső; Terbe, Erika (Slavia Centralis, 2020)
The Atlas of Hungarian Dialects in Romania is nearly finishedThe 11th and last volume of The Atlas of Hungarian Dialects in Romania (RMNyA) is ready for publication. The work, the material of which was gathered in the 1950s and 1960s, is suppletory in Hungarian dialectology. The RMNyA enables a more detailed description of the Hungarian dialects in Romania and a comprehensive typology of dialects. It opens new possibilities for synchronic and diachronic examinations. Concurrently with its publication, the RMNyA was included in the project for the digitalisation of the MNyA, as a result of which the two big atlases are integrated into a single electronic database. This enables new corpus linguistical and dialectological analyses as well as the preparation of integrated maps by using the techniques of computer cartography.
Keywords: Hungarian dialects in Romania; linguistic atlas; geolinguistics; incorporation of atlases; digitalisation